(untitled) (Journal of Economics and Management Research, 2025)
ملخص: يهدف البحث إلى محاولة معرفة مدى مساهمة التجزئة المثلى للمنتجات في السوق في زيادة مبيعات وربحية المؤسسة، الدراسة شملت بيانات لمبيعات الزيوت في خمسة وثلاثون محطة خدمية لتوزيع الوقود التابعة لمؤسسة نفطال -المقاطعة التجارية سعيدة- والتي ثضم ست ولايات سعيدة، معسكر، البيض، النعامة، بشار و تندوف وذلك خلال خمس سنوات من سنة 2014 إلى غاية سنة 2018 وقد توصلت الدراسة بعد استخدام برامج SPSS عن طريق تحليل TURFإلى الأهمية النسبية للتجزئة السوقية في تشكيل التركيبات المثلى لمنتجات الزيوت في مؤسسة نفطال ومدى انعكاسها على مردودية المؤسسة. Abstract: The aim of the research is to try to determine the extent to which the optimal retailing of products in the market contributed to the increase in sales and profitability of the organization. The study included data on oil sales in 35 fuel service stations belonging to the Naftal Commercial District - The study, after the use of SPSS programs through the analysis of the TURF to the relative importance of market segmentation in the formation of optimal combinations of oil products In an institution And the extent of their reflection on the profitability of the institution. .